(untitled) (Comparatismi, 2020)
In questo breve intervento conclusivo l’autore riprende le linee principali del dibattito, sottolineando la necessità di un profondo rinnovamento degli studi letterari, e delineando un significato più ampio per la comparatistica in rapporto all’esperienza. __ In this brief article, Giovanni Puglisi takes up the main points of the debate as presented in the articles that precede it, emphasizing the need for a renewal of literary studies, and outlining a broader meaning for Comparative Literature studies in relation to experience.